Determinants of School Efficiencies from Innovative Teaching through Digital Mobile E-Learning for High Schools: Application of Bootstrap Truncated Regression Model - Liu, Hsiang-Hsi; Kuo, Fu-Hsiang (Asian Journal of Economic Modelling, 2017)
The goal of this research is to evaluate the innovative teaching to affect school efficiency through using digital mobile e-learning of high school in Taiwan. Based on data envelopment analysis (DEA) and bootstrap truncated regression (BTR) model. The empirical results of this research indicate the following results: (1) Importing digital mobile e-learning can really enhance the efficiency of school management. (2) The results suggested in BTR model justifies that among the eight-factor analyses, six factors were overestimated and the factors with total equipment expenses and teacher-student ratio were under estimated by Tobit regression model (TRM). Also, the results for the effects of school location and school attribute on school’s operational efficiency were non-significant in TRM. In comparison, the estimated effects of school location and school attribute on school’s operational efficiency by BTR in this study are significant. Therefore, the factors studied here may be important in explaining the determinants of school efficiencies from innovative teaching through digital mobile e-Learning. To increase students learning effectiveness in school, it is necessary to first add school size, Tablet PC numbers, and technical teachers. However, the result shows total equipment expenses associated with tablet PC have a small negative influence on school management efficiency. On the other hand, the results show that the effect of school location, school attribute and school high-vocational attribute on school’s operational efficiency have significant. Mainly, the degree of school’s operational efficiency also needs to be taken into account their school attributes such as equipment, teaching quality, management decisions and etc. by digital mobile e-learning.